2020
DOI: 10.31014/aior.1992.03.03.262
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy and Corporate Financial Performance: Evidence from Selected Listed Consumer Goods Firms in Nigeria

Abstract: The Journal of Economics and Business is an Open Access publication. It may be read, copied, and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…According to Velnampy, Nimalthasan and Kalaiarasi (2014), it stated that the relationship between dividend pay-out ratio and return on equity is not significance. This result is consistent with Narang (2018); Musa et al (2020); Ugwu, Onyeka and Okwa (2020); Cyril, Emeka and Cheluchi (2020) who found that there was a positive and insignificant between the variables.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to Velnampy, Nimalthasan and Kalaiarasi (2014), it stated that the relationship between dividend pay-out ratio and return on equity is not significance. This result is consistent with Narang (2018); Musa et al (2020); Ugwu, Onyeka and Okwa (2020); Cyril, Emeka and Cheluchi (2020) who found that there was a positive and insignificant between the variables.…”
Section: Discussionsupporting
confidence: 91%
“…A related study by Ugwu, Onyeka and Okwa (2020). The researchers conducted the study for consumer good firms in Nigeria on dividend policy and corporate financial efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firm characteristics and dividend policy Ugwu et al (2020) studied the Consumer Goods Sector in Nigeria, using correlation and ex-post facto research designs for data from 2015 to 2019, and found a significant positive relationship between firm characteristics and dividend policy. Likewise, Sanyaolu et al (2019), in their study of the Food and Beverage Sector of the Nigerian exchange, using panel data analysis on data from 2008 to 2016, reported a significant positive influence of firm characteristics on dividend policy.…”
Section: 21mentioning
confidence: 99%
“…The research findings indicate that companies with higher profitability, lower leverage, good liquidity, and larger size tend to experience lower underpricing during an IPO. This indicates that companies with strong financial performance and larger size have higher attractiveness to investors, resulting in their IPO stock prices tending to approach their true value (Daniswara & Daryanto, 2020;Ugwu et al, 2020;Lim & Rokhim, 2021;Basdekis et al, 2023;Jatoi & Rasheed, 2023;Karima & Ghazali, 2023;Will & Simorangkir, 2023). Additionally, research also shows that non-financial information factors such as Company Age, Auditor Reputation, Underwriter, and Industry Type also influence the level of underpricing.…”
Section: Introductionmentioning
confidence: 99%